Rechtvinding Dalam Sengketa Perdata: Analisis Metode Penemuan Hukum Dalam Putusan Mahkamah Agung Nomor 46/K/Pdt/2006 - Tasya Gita Irwanda; Irwan Triadi (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study analyzes the forms and methods of legal discovery (rechtvinding) employed by the Supreme Court Justices in Decision No. 46/K/Pdt/2006, particularly in determining the existence of an unlawful act and assessing the legal reasoning that underlies the judgment. The analysis focuses on how the judges conducted interpretation, legal construction, and the application of legal principles to address gaps or ambiguities in the norms governing civil dispute resolution. Using a normative juridical research method with a case approach, this study finds that the judges applied a combination of systematic interpretation, teleological interpretation, and legal construction through the application of expanded legal principles as developed in jurisprudence. The judges not only applied Article 1365 of the Indonesian Civil Code formally but also engaged in progressive legal discovery by assessing the substance of the defendant’s actions in light of the fundamental purpose of protecting the civil rights of the parties. The study demonstrates that the legal discovery performed in this decision reflects a shift from mere law application toward law creation oriented toward substantive justice. These findings are expected to contribute to the development of jurisprudential studies and civil adjudication practices in Indonesia, particularly concerning the formulation of the boundaries of unlawful acts through responsive and well-reasoned methods of legal discovery.